2022
DOI: 10.1155/2022/9315283
|View full text |Cite
|
Sign up to set email alerts
|

m6A-Related lncRNAs Predict Overall Survival of Patients and Regulate the Tumor Immune Microenvironment in Osteosarcoma

Abstract: Background. m6A-related lncRNAs have demonstrated great potential tumor diagnostic and therapeutic targets. The goal of this work was to find m6A-regulated lncRNAs in osteosarcoma patients. Method. The Cancer Genome Atlas (TCGA) database was used to retrieve RNA sequencing and medical information from osteosarcoma sufferers. The Pearson’s correlation test was used to identify the m6A-related lncRNAs. A risk model was built using univariate and multivariable Cox regression analysis. Kaplan–Meier survival analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Such as, Chen et al reveled that hyper-methylated hsa_circ_0007259 activated STAT3 signaling pathway via sponge miR-21-5p and could be acted as a potential biomarker in RA [ 215 ]. Besides, it has been reported that m6A-related lncRNAs regulated the tumor immune microenvironment and predicted the overall survival of OS patients [ 190 , 216 ]. Although researchers have made progress in exploring the diagnosis value of m6A methylation in SSD, further detailed studies are needed to verify the effectiveness, accuracy and feasibility of these findings in larger samples.…”
Section: Discussionmentioning
confidence: 99%
“…Such as, Chen et al reveled that hyper-methylated hsa_circ_0007259 activated STAT3 signaling pathway via sponge miR-21-5p and could be acted as a potential biomarker in RA [ 215 ]. Besides, it has been reported that m6A-related lncRNAs regulated the tumor immune microenvironment and predicted the overall survival of OS patients [ 190 , 216 ]. Although researchers have made progress in exploring the diagnosis value of m6A methylation in SSD, further detailed studies are needed to verify the effectiveness, accuracy and feasibility of these findings in larger samples.…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, high expression of PGK1 can promote glycolysis and proliferation of osteosarcoma cells [ 154 ]. Besides, Bi et al analyzed seven prognostic m6A related lncRNAs in osteosarcoma and found that they play an important role in the glycolysis process of osteosarcoma [ 155 ].…”
Section: M6a Regulates Tumor Glycolysismentioning
confidence: 99%
“…Moreover, LINC00538 was positively correlated with resting dendritic cells and negatively linked to activated dendritic cells in our results. m6A-associated lncRNAs are closely associated with the immune microenvironment of osteosarcoma tumours and may influence tumour occurrence and progression [ 80 ]. These findings reveal new directions in the role of m6A and lncRNA in the immune microenvironment of osteosarcoma and demonstrate that m6A modification may be a potential therapeutic target for anti-tumour immunotherapy.…”
Section: M6a and Ncrna In The Osteosarcoma Microenvironmentmentioning
confidence: 99%